PENGARUH MOTIVASI TERHADAP KINERJA PETERNAK SAPI POTONG - Faisal Dako; Suparmin Fathan; Sri Yeni Pateda (Gorontalo Journal of Equatorial Animals, 2023)
The purpose of this study was to determine the effect of motivation on the performance of farmers and the level of motivation of beef cattle farmers in Limehu Village, Tabongo District, Gorontalo Regency. The research method used is a survey method by preparing primary and secondary data. Descriptive analysis was used to determine the level of motivation while simple linear regression analysis was used to determine the effect of motivation on farmer performance. The results showed that the level of motivation on the performance of farmers in Limehu Village, Tabongo District, Gorontalo Regency was included in the very high category with a score of 1688. This was due to internal and external factors having a significant effect on farmer motivation. The effect of farmer motivation on performance is obtained by the correlation coefficient (r) 1.5 and the coefficient of determination (r2) 0.015 which shows that the influence of motivation on performance is 1.5%.